Dampak Pandemi Covid-19 terhadap Tenaga Kerja Formal di Indonesia - Dewi Middia Martanti; Florentz Magdalena; Natalia Pipit D. Ariska; Nia Setiyawati; Waydewin C. B. Rumboirusi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2020)
Even though the informal labour still dominates Indonesia workforce, the trend of formal labour increases each year. BPS data shows that in 2015, the percentage of formal labor reached 42,25 percent. Then it increased to 44,28 percent in 2019. As a capital-intensive sector, formal sector supports economy of Indonesia, because it is relatively safe or less prone to shut down. However, the determination of the global pandemic status on March 11, 2020 due to Corona Virus Disease (Covid-19) has hit the world economy, including Indonesia. To suppress the spread of Covid-19, people are asked to work, study, or pray from home. This causes many companies suffer losses and even close their businesses, thus impacting workers. Based on data from the Ministry of Manpower 13 April 2020 as many as 1.2 million formal labour have been furloughed and 212.4 thousand have been laid off. This study aims to observe the trends of formal labour in Indonesia and the impact of Covid-19 on formal labour in Indonesia. This study uses secondary data obtained from various sources which are analyzed descriptively.